2014
DOI: 10.1021/am503722t
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Three-Dimensional (3D) Raspberry-Like Copper Chromite Spinel Catalyst in a Facile Hydrothermal Route and Its Activity in Selective Hydroxylation of Benzene to Phenol

Abstract: Three-dimensional (3D) raspberry-like CuCr2O4 spinel nanoparticles were prepared hydrothermally in the presence of cationic surfactant, cetyltrimethylammonium bromide (CTAB). Detailed characterization of the material was carried out by X-ray diffraction (XRD), inductively coupled plasma-atomic emission spectroscopy (ICP-AES), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…Moreover, no obvious diffraction peaks of GO or carbon were detected, which indicate that GO was completely converted into rGO after heat treatment at 180 °C for 3 h. The FT-IR spectra of CCO versus CCO@RGO and GO versus RGO are displayed in Fig. S3a, b [37, 43]. It can be observed that the FT-IR spectra are very similar to the CCO@rGO nanocomposite and CCO nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no obvious diffraction peaks of GO or carbon were detected, which indicate that GO was completely converted into rGO after heat treatment at 180 °C for 3 h. The FT-IR spectra of CCO versus CCO@RGO and GO versus RGO are displayed in Fig. S3a, b [37, 43]. It can be observed that the FT-IR spectra are very similar to the CCO@rGO nanocomposite and CCO nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…So, a general and simple strategy is highly desirable for synthesis of supported nanostructure materials. During last few years, our group is engaged in developing surfactant induced preparation of Cu, Ag and Pt based nanomaterials supported on different nanostructured oxides like Cr 2 O 3 , WO 3 , CeO 2 , Mn 3 O 4 , etc in a single preparation method . We report here highly dispersed Ni‐nanoparticles supported on nanocrystalline ZrO 2 in a single preparation method for chemoselective hydrogenation of nitroarenes, at 60 °C under 1.0 MPa H 2 in water .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of nanoscience and nanotechnology, nanostructured materials have been attracted much more researchers' attention in the fields of catalytic materials [1] and gas-sensing materials [2], especially in electrochemical energy storage and conversion materials [3]. In addition, transition metal oxides have been gradually applied as important components for electrode materials.…”
Section: Introductionmentioning
confidence: 99%